PENGARUH PELAKSANAAN PELATIHAN DAN IKLIM ORGANISASI TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. TOYOTA ASTRA FINANCE PEKANBARU - Yulia Sriulina Tarigan; Seno Andri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
This study aims to determine how much influence the implementation of training and organizational climate on employee job satisfaction at PT. Toyota Astra Finance Pekanbaru. Implementation of Training as a variable (X1), Organizational Climate as a variable (X2), and Work objectives as a variable (Y). The method in this study is descriptive and quantitative using the SPSS ver 23 for windows program, where the sample in this study was taken as many as 32 respondents and the research technique used was census. From the results of data analysis which includes validity test, reliability test, simple linear regression test, multiple linear regression test, determination test, t test, and f test. So it can be said that the implementation of training has a significant effect on employee job satisfaction. Organizational climate has a significant effect on employee job satisfaction. Implementation of Training and Organizational Climate affect employee job satisfaction at PT. Tpypta Astra Finance Pekanbaru. Keywords : Implementation of Training, Organizational Climate, Work Objectives